1997
DOI: 10.1007/s001340050369
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome in a community hospital ICU

Abstract: These data show that for ARDS, at least, mortality outcome can be comparable in a community ICU to a tertiary referral institution. The pattern of disease in an urban Australian community hospital is different to that often reported from tertiary centres. The incidence of ARDS in an Australian urban community is comparable to the reported incidence in North America and Western Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 35 publications
3
17
1
1
Order By: Relevance
“…The mortality in our series was not related to the timing of the ARDS appearance and this was not different from that reported by Croce et al [27]. The only therapeutic measure that was related to the prognosis was the initial resuscitation, as reported by other researchers [26].…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…The mortality in our series was not related to the timing of the ARDS appearance and this was not different from that reported by Croce et al [27]. The only therapeutic measure that was related to the prognosis was the initial resuscitation, as reported by other researchers [26].…”
Section: Discussionsupporting
confidence: 64%
“…We found that mortality was not predicted by age, however this may be because we had young patients with a mean age of 36 years. Significant differences could have been expected had the patients been older and less homogeneous [22,25,26]. The mortality in our series was not related to the timing of the ARDS appearance and this was not different from that reported by Croce et al [27].…”
Section: Discussioncontrasting
confidence: 32%
“…One of the most frequently studied indices is the Pa,O 2 / FI,O 2 , although contradictory results concerning its ability to predict outcome have been reported in adult AHRF/ARDS [2,[27][28][29][30][31][32][33][34][35]. Some authors have argued that the ratio may not be predictive at inclusion, but after 24 or 48 h [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…ARDS mortality decreased over the years probably also thanks to the improved therapeutic management of the ventilatory settings (60,63,(100)(101)(102). In the early 90s, Nolan and colleagues reported a hospital mortality of 59% in moderate and severe ARDS in a population based study conducted in Australia (87). BrunBuisson et al described similar findings in the late 90s, in a hospitalization based study conducted in 78 ICUs in Europe, with a proportion of 57.9% even including mild ARDS (83).…”
Section: Ards Mortality-still a Critical Challengementioning
confidence: 99%